2020
DOI: 10.1001/jama.2020.9935
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diagnosis Coding With Differences in Risk-Adjusted Short-term Mortality Between Critical Access and Non–Critical Access Hospitals

Abstract: IMPORTANCE Critical access hospitals (CAHs) provide care to rural communities. Increasing mortality rates have been reported for CAHs relative to non-CAHs. Because Medicare reimburses CAHs at cost, CAHs may report fewer diagnoses than non-CAHs, which may affect risk-adjusted comparisons of outcomes.OBJECTIVE To assess serial differences in risk-adjusted mortality rates between CAHs and non-CAHs after accounting for differences in diagnosis coding. DESIGN, SETTING, AND PARTICIPANTSSerial cross-sectional study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Prior studies have shown that when payment policy changes drive changes in coding intensity, it can complicate trend analyses of risk-adjusted outcomes. 15,16…”
Section: Jama Health Forum | Original Investigationmentioning
confidence: 99%
“…Prior studies have shown that when payment policy changes drive changes in coding intensity, it can complicate trend analyses of risk-adjusted outcomes. 15,16…”
Section: Jama Health Forum | Original Investigationmentioning
confidence: 99%
“…to more accurately capture their patients' disease severity; and (3) in the absence of clear guidance of when upcoding is appropriate (or effective safeguards against this practice), US hospitals have increased upcoding to improve reimbursement and their apparent performance in quality assessment programs. 3,4,[6][7][8] All 3 elements may be contributing factors, although it is currently unclear what the respective contributions are. An inability to disentangle actual quality signals from those distorted by inaccurate coding practices is a potential threat to the goals of efficiently improving quality and ensuring the validity and reliability of the data provided by existing quality assessment programs.…”
Section: Strategies To Enhance the Reliability Of Administrative Codingmentioning
confidence: 99%
“…Because administrative data (ie, diagnosis and procedural codes) are standardized and can be accessed at a low cost in virtually every practice setting, these codes are commonly used to construct process and outcome quality measures used in value-based payment and quality assessment programs.Although the use of administrative data for quality measurement is convenient, this approach creates opportunities to "game the system" because hospitals can optimize their coding practices to maximize reimbursement or perceived performance. [3][4][5][6] For outcome quality measures, risk adjustment has a critical role by accounting for underlying variation in the level of risk across patient populations, thereby ensuring that measurement, comparisons, and reimbursement are fair…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their article, Bilimoria and Pawlik 1 state that "the use of RSMR as a quality proxy has been criticized on both theoretical and methodological grounds", supporting this claim with literature predominately published in the 1990s. Within the past 20 years, however, methodological approaches have improved considerably (for example, owing to the better understanding and reliability of coding practices, differences between hospital RSMRs and their effects on long-term survival outcomes) 3,4 .…”
mentioning
confidence: 99%